Enhanced electron field emission of Cu implanted microcrystalline diamond films after annealing. (December 2016) - Qi, Ting; Dong, Lijuan; Qiao, Yu; Yu, Shengwang; Hei, Hongjun; He, Zhiyong; Zhang, Yixin; Jia, Yuxin; Zhang, Chao; Shen, Yanyan
Abstract: Effects of Cu ions implantation on the structure and electron field emission (EFE) properties of microcrystalline diamond (MCD) films were investigated. The MCD films implanted with Cu ions at a fluence of 1.0 × 10 17 ions/cm 2 and subsequent annealing in N2 atmosphere at 600 °C for 2 h achieved good electrical conductivity with lower surface resistance of 0.1301 Ω/sq, high carrier concentration of 7.621 × 10 18  cm −3 and hall mobility of 62 cm 2  V −1 s −1 . Our results show that Cu nanoparticles can be formed in surface of MCD films after Cu ion implantation and annealing, which induced the formation of graphitic phases during annealing process. Consequently, the presence of Cu nanoparticles and graphitic phase formed conduction channels for efficient electron transport, ensuing better electron field emission (EFE) properties for Cu ion implanted/annealed MCD film with low turn-on field of 2.234 V/μm and high EFE current density of 28.560 μA/cm 2 at an applied field of 4.172 V/μm. Highlights: The EFE of Cu implanted MCD films were successfully enhanced after annealing. The EFE behavior of Cu-implanted/annealed film can be turned on at E0  = 2.234 V/μm. Surface roughness of the MCD films was changed significantly. The increase of graphites has enhanced the EFE properties of MCD films.